The challenges of current ATM interface for low vision people / Roslina Ahmed Tajuddin - Ahmed Tajuddin, Roslina (2009)
The use of Automated Teller Machine (ATM) has becoming demanding day by day. Various transactions can be done without the need to go to the banks. Each machine operated in many places without any connection to the banking systems, and transaction took place based on the information recorded in the magnetic bands of the cards. (Mario Yanez, Jr, 1997). ATM is been used by various type of people including impaired people. Blind ones, low vision people; handicap people are those who are categorized as the one who has the disabilities. The current ATM interface is only designed for normal people without concern the people who are disable especially the low vision people. Thus, the purpose of this study is to improve the ATM interface mainly dedicated for the low vision people. This ATM will be redesigned based on the existing interface. In order to make a good design interface to cater the low vision people, this research is based on universal design principles approach. Conducting this research provides benefits to the low vision communities, the banking institutions and the developer. Besides, it also enhances the awareness to the banking institutions the difficulties that low vision had in making transaction via ATM.